Pengaruh Pencampuran Air Laut Dan Air Tawar Terhadap Struktur Fisik Estuaria - Gulo, Paskalis; Waruwu, Formas; Lase, Eduard Moris (CV. SINAR HOWUHOWU, 2025)
Estuaries are semi-enclosed coastal waters where seawater and freshwater from land meet. The mixing of these two types of water creates complex physical conditions, affecting salinity, temperature, substrate and current dynamics. This study aims to analyze the influence of seawater and freshwater mixing on the physical structure of estuaries, focusing on stratification patterns, salinity distribution and hydrodynamics. The research method involved a literature review of various current scientific sources. Results show that mixing patterns are strongly influenced by factors such as freshwater discharge, tides, and estuarine bottom topography. Understanding these dynamics is important for the sustainable management of estuarine ecosystems.